Craniofacial Trauma Diagnosis and Management - Hardt, Nicolas; Kuttenberger, Johannes; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The book covers the entire scope of traumatology in the important border area between the neuro- and viscerocranium. It focuses on diagnostic operation planning and the interdisciplinary management of craniofacial injuries. In the first part, the classification and epidemiology of craniofacial fractures are outlined and specific problems are discussed. The second part deals with radiologic diagnostics and basic neurosurgical measures. The main part of the book covers operative principles and a step-by-step description of hard and soft tissue reconstruction after craniofacial trauma. Complications of craniofacial injuries and late reconstruction of craniofacial defects, including computer-assisted planning, are covered in the final part.
Classification and Diagnosis -- Anatomy of the Craniofacial Region -- Radiology of Craniofacial Fractures -- Classification of Craniofacial Fractures -- Mechanisms of Craniofacial Fractures -- Epidemiological Aspects of Craniofacial/Skull Base Fractures -- Craniofacial Fracture Symptoms -- Neurocranial Injuries in Craniofacial/Skullbase Fractures -- Therapy -- Surgical Repair of Craniofacial Fractures -- Methods of Dural and Skull Base Treatment -- Bone Grafts -- Osteosynthesis of Craniofacial Fractures -- Surgical Strategy for Complex Craniofacial Fractures -- Complications and Late Sequelae Following Craniofacial Reconstruction -- Delayed Reconstruction of Frontofacial Defects and Deformations -- A Treatment Algorithm in Craniofacial Reconstruction: Future Developments.
Keywords: Medicine; Neurosurgery; Head -- Surgery; Surgery; Medicine & Public Health; Oral and Maxillofacial Surgery; Neurosurgery; Head and Neck Surgery; General Surgery